Tokoh Ulama Hadis Kontemporer di Dunia dan di Indonesia - R, Rian; T, Tasbih; Z, Zaenab (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Hadith, as the second source of Islamic law after the Qur'an, has undergone significant development in both methodology and the figures involved. This study aims to comprehensively describe the biographies and thoughts of contemporary hadith scholars, both globally and specifically in Indonesia. This research uses a qualitative method with a literature study approach. The results show that Yusuf al-Qardhawi and Muhammad al-Ghazali represent global scholars who have contributed significantly to the development of rational, contextual, and critical approaches in hadith studies. In Indonesia, Ali Mustafa Yaqub and Muhammad Syuhudi Ismail are key figures who have laid the foundations for a scientific and systematic study of hadith, while providing constructive criticism against orientalist views. Their thoughts emphasize the importance of isnad and matn criticism, contextual understanding, and the defense of the authenticity of hadith in facing contemporary challenges.